PERAN TERAPI PERILAKU DENGAN MENGGUNAKAN REINFORCEMENT POSITIF TERHADAP ORANG DEWASA YANG MENGALAMI RETARDASI MENTAL - Supriyono, Yoyon (Jurnal Interaktif, 2010)
The purpose of this research is to understand how applying the therapy of behavior. The method used in this research is by using positive reinforcement for adult who experiences in mental retardation, combined with optimizing family role. These methods are believed contribute to the increase of independence of the subject. Subject on this case is an adult which has age 30 years old. The subject never has psychological test. Based of Binet test, the intelegency he got is 7 (value IQ), so that based of category on DSM IV, the subject is experiencing of mental retardation on seriously category.Method Assessments used to take the data from subject are: interview, observation, formal test, and informal test. The result of assessment is that got little stimulus from family. The lack of stimulus cause the subject have high dependence to others in doing simple work for example: take a bath, eat.Pursuant to case background which wish handled, so in finishing it subject will be given the intervention with the behavioral therapy by using positive reinforcement, previously family will give consultancy, so they can support in course of therapy. The step on this therapy is to make new behavior, that is train the subject in conducting walk of life for example: eat, take a bath, clean of self after defecating, helping the simple work (moping). The result of intervention shows that stimulus gift intensively and continuously will improve the behavioral ability of the subject.Keywords: behavior theraphy; positive reinforcement; adult; mental retardation